2020
DOI: 10.1177/0148558x20920986
|View full text |Cite
|
Sign up to set email alerts
|

Does Ex Ante Severance Pay Affect the Timeliness of Bad News Disclosure? The Role of Managerial Exit Costs

Abstract: Extant literature documents a positive association between ex ante severance pay and timeliness of bad news disclosure, suggesting that the provision of severance pay is consistent with efficient contracting. Relying on an empirically unexplored theory, we investigate whether and how managerial exit costs (i.e., financial and nonfinancial losses triggered by employment termination) affect the effectiveness of severance pay in curbing bad news withholding. We find that managerial exit costs attenuate the positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…Chen et al (2015), who found that this effect is particularly pronounced for severance agreements of greater value or duration, affirm this conclusion. Studies have also identified other relevant contextual factors that can amplify the positive relationship between severance agreements and risk-taking, such as executives having a high-variable pay structure (Ling, 2012) or more promising career prospects outside of the firm (Akamah, Brockbank, & Shu, 2022).…”
Section: Literature Review: What We Knowmentioning
confidence: 99%
“…Chen et al (2015), who found that this effect is particularly pronounced for severance agreements of greater value or duration, affirm this conclusion. Studies have also identified other relevant contextual factors that can amplify the positive relationship between severance agreements and risk-taking, such as executives having a high-variable pay structure (Ling, 2012) or more promising career prospects outside of the firm (Akamah, Brockbank, & Shu, 2022).…”
Section: Literature Review: What We Knowmentioning
confidence: 99%